Inhibition of orexin-1/hypocretin-1 receptors inhibits yohimbine-induced reinstatement of ethanol and sucrose seeking in Long–Evans rats - Richards, Jemma K.; Simms, Jeffrey A.; Steensland, Pia; Taha, Sharif A.; Borgland, Stephanie L.; Bonci, Antonello; Bartlett, Selena E. (Psychopharmacologia, 2008)
Rationale Previous studies have shown that orexin-1/hypocretin-1 receptors play a role in self-administration and cue-induced reinstatement of food, drug, and ethanol seeking. In the current study, we examined the role of orexin-1/hypocretin-1 receptors in operant self-administration of ethanol and sucrose and in yohimbine-induced reinstatement of ethanol and sucrose seeking. Materials and methods Rats were trained to self-administer either 10% ethanol or 5% sucrose (30 min/day). The orexin-1 receptor antagonist SB334867 (0, 5, 10, 15, 20 mg/kg, i.p.) was administered 30 min before the operant self-administration sessions. After these experiments, the operant self-administration behaviors were extinguished in both the ethanol and sucrose-trained rats. Upon reaching extinction criteria, SB334867 (0, 5, 10 mg/kg, i.p.) was administered 30 min before yohimbine (0 or 2 mg/kg, i.p.). In a separate experiment, the effect of SB334867 (0, 15, or 20 mg/kg, i.p.) on general locomotor activity was determined using the open-field test. Results The orexin-1 receptor antagonist, SB334867 (10, 15 and 20 mg/kg) decreased operant self-administration of 10% ethanol but not 5% sucrose self-administration. Furthermore, SB334867 (5 and 10 mg/kg) significantly decreased yohimbine-induced reinstatement of both ethanol and sucrose seeking. SB334867 did not significantly affect locomotor activity measured using the open-field test. Conclusions The results suggest that inhibition of OX-1/Hcrt-1 receptors modulates operant ethanol self-administration and also plays a significant role in yohimbine-induced reinstatement of both ethanol and sucrose seeking in rats.